The effects of naturalization on immigrants' employment probability (France, 1968 - 1999) - Denis Fougère; Mirna Safi (Institute for the Study of Labor (IZA), 2008)
Naturalization is usually regarded as an important sign of civic and political integration amongst immigrants, but it can also be seen as a factor of their economic integration. The aim of this study is to analyze the naturalization phenomenon in France and examine its link with the immigrants' labor force status. We use longitudinal data from the Echantillon Démographique Permanent (EDP) sample. The EDP is a panel dataset by which we can follow almost 1% of the French population from 1968 to 1999 through information contained in the 1968, 1975, 1982, 1990 and 1999 French census. The sample we use (N = 36,685) is limited to immigrants who declared themselves non-naturalized at the time they first appeared in the panel. This makes it possible for us to observe possible changes of nationality between two census dates and their potential consequences on the employment probability at the second date. In our study, the probability of naturalization between two census dates not only depends on observable individual characteristics of immigrants (country of birth, age, marital situation, occupation, human capital, etc.), but also on a number of contextual variables related to the role of the community in the assimilation process (size of the community and number of foreigners in the region of residence). We compare the differential rates of naturalization between the various ethnic groups and try to answer the following question: are there differences between the naturalized immigrant population and the immigrant population as a whole? In the second stage, we analyze the effect of naturalization on the individual employment probability by estimating a univariate probit model. To control for the potential endogeneity of the naturalization process, we also estimate a bivariate probit model. With both models, we find that naturalization has a significant positive effect on immigrants' employability and that this effect is particularly high for groups of immigrants who have a low probability of employment in the host country.
Keywords: F22; 330; Immigration; naturalization; citizenship; employment; Migranten; Einwanderung; Staatsangehörigkeit; Berufliche Integration; Soziale Integration; Frankreich